FPIES in exclusively breastfed infants: two case reports and review of the literature - Francesco Baldo; Martina Bevacqua; Cristiana Corrado; Daniela Nisticò; Laura Cesca; Valentina Declich; Roberto Dall'Amico; Egidio Barbi (BMC, 2020)
Abstract Background Food Protein-Induced Enterocolitis Syndrome (FPIES) is a non IgE-mediated food allergy that generally affects children in the first year of life. Usually symptoms break out when formula milk or solid foods are introduced for the first time but they might also appear in exclusively breastfed infants, since the trigger elements, especially cow's milk proteins, can be conveyed by maternal milk as well. FPIES in exclusively breastfed babies is a very rare clinical condition and only few cases have been reported in the medical literature. Case presentation We describe two cases of FPIES in exclusively breastfed babies. The first one is a two-month-old infant with a brief history of vomit and diarrhea that presented to the Emergency Department in septic-like conditions. The main laboratory finding was a significant increase in methemoglobin (13%). Clinically, we noted that, when breastfeeding was suspended, diarrhea drastically improved, and vice versa when maternal milk was reintroduced. An amino acid-based formula allowed a complete normalization of the symptoms. The second one is a three-month-old infant admitted for a 3 days history of persistent vomit and diarrhea. Blood tests showed a raised level of methemoglobin (7%). An esophagogastroduodenoscopy was performed and biopsies showed an eosinophilic infiltration of the duodenal mucosa. A maternal exclusion diet and an amino acid-based formula allowed a rapid regularization of the bowel function. Conclusions We searched all the cases of FPIES in exclusively breastfed babies reported in the medical literature, identifying eight patients, with an average age of 3 months (range 15 days - 6 months). The majority of the cases were initially diagnosed as gastroenteritis or sepsis, five cases were characterized by an acute on chronic scenario and cow's milk was the most frequently involved food. Methemoglobin was never tested. An oral food challenge test was performed in two patients. FPIES in exclusively breastfed infants is a rare condition that, in the presence of compatible history and symptoms, should be considered also in exclusively breastfed babies. The evaluation of methemoglobin can simplify the diagnostic process.